The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2021
DOI: 10.21511/im.17(3).2021.05
|View full text |Cite
|
Sign up to set email alerts
|

Consumption trends of milk and dairy products in Slovakia and its comparison with other V4 countries

Abstract: Milk consumption is a very important part of consumers’ daily diet due to its positive health effect. The purpose of the paper is to evaluate the market of milk and dairy products. The paper analyzes the development of milk consumption in V4 countries, which was described by using regression functions. The data were obtained from the statistical offices of chosen countries. Based on the achieved results it was found that in Slovakia and Hungary milk consumption is very low, but in the Czech Republic and Poland… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…The transition from conventional farming to organic farming presents farmers with economic risks, including potential decreases in sales due to lower crop yields. However, this transitional period typically lasts 2-3 years, after which farmers often begin to experience economic benefits [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…The transition from conventional farming to organic farming presents farmers with economic risks, including potential decreases in sales due to lower crop yields. However, this transitional period typically lasts 2-3 years, after which farmers often begin to experience economic benefits [34,35].…”
Section: Discussionmentioning
confidence: 99%
“…Based on the results obtained, Kubicová et al (2021) found that milk consumption in Slovakia and Hungary is very low, while in the Czech Republic and Poland, milk consumption is recorded within the range of recommended rations, i.e. it is sufficient.…”
Section: Introductionmentioning
confidence: 95%